Fruquintinib effectively controlled the advanced small bowel adenocarcinoma progressed after multiple lines of palliative treatment: a case report and literature review - Ding, Yuwei (Cancer Biol Ther, 2020)
Small bowel cancer is a very rare disease. It can be treated by surgery at early stages; however, there is no standard therapeutic strategy established for the treatment of unresectable and/or metastatic diseases. Here we present a case of metastatic small bowel adenocarcinoma, which progressed after sequential treatment with XELOX (capecitabine and oxaliplatin), FOLFIRI (fluorouracil, leucovorin, and irinotecan), cetuximab, HER-2 targeted therapy and apatinib and was then effectively controlled by fruquintinib. Genetic testing showed wild-type KRAS/NRAS/BRAF, HER-2 amplification, and microsatellite stable. Then the patient started to receive fruquintinib and has already achieved a 6-month progression-free survival. Till Jun 2019, the treatment with fruquintinib is still ongoing and no severe adverse effect has been seen so far. Although fruquintinib is not, at present, a standard therapeutic strategy recommended by the treatment guideline for advanced small bowel adenocarcinoma, the significant curative effect has been seen in our clinical practice.